2004
DOI: 10.1007/s10792-004-1957-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-related modifications of the corneal endothelium in adults

Abstract: Topographical distribution of the corneal endotheliul cell density is maintained lifelong. Age-related changes involve both center and periphery. The higher peripheral decrement observed in the ancient subjects could be considered as a major finding and in elderly a topographical disparity might occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 17 publications
(30 reference statements)
1
22
0
1
Order By: Relevance
“…7,11,12 Notwithstanding these discrepancies in specimen selection or sampling strategy, it is surely not appropriate to simply dismiss in vivo studies in which a distinct difference has not been detected between the central and midperipheral regions 9,11 and there are reports of lower cell density values for the more peripheral cornea. 4,10 The main conclusion from the current study is that a history of prolonged soft contact lens wear could be a determinant of the apparent difference between central and at least paracentral endothelial cell density or the replication competence versus senescence of these cells.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…7,11,12 Notwithstanding these discrepancies in specimen selection or sampling strategy, it is surely not appropriate to simply dismiss in vivo studies in which a distinct difference has not been detected between the central and midperipheral regions 9,11 and there are reports of lower cell density values for the more peripheral cornea. 4,10 The main conclusion from the current study is that a history of prolonged soft contact lens wear could be a determinant of the apparent difference between central and at least paracentral endothelial cell density or the replication competence versus senescence of these cells.…”
Section: Discussionmentioning
confidence: 67%
“…4 Other publications on younger and older subjects have reported the MPCD or peripheral cell density values to be slightly lower 11 or notably lower than the CCD values. 4,10 Further studies and analyses are required to find out why this may be the case and seen not only in approximately 20% of the current study on contact lens wearers but also in spectacle wearers (unpublished data).…”
Section: Discussionmentioning
confidence: 91%
“…Such a compromise is most frequently associated with age, hypoxia due to contact lens wear, systemic disease such as diabetes mellitus, and ocular surgery [1,2,[4][5][6][7][8][9]. The quantitative evaluation of the endothelial tissue relies on the evaluation of different parameters such as the endothelial cell density (ECD), average cell size (ACS), coefficient of variation of cell surface (CV), or hexagonality index (HI).…”
Section: Discussionmentioning
confidence: 99%
“…Age is a significant cause for endothelial cell loss [3,4]; however, other factors such as contact lens wear [5,6], diabetes mellitus [7], intraocular surgery including cataract surgery [8,9], and penetrating keratoplasty [10] have been demonstrated to be associated with significant endothelial cell loss.…”
Section: Introductionmentioning
confidence: 99%
“…The primary cause of ECD loss over time is time itself, with cell density inversely related to age ( Figure 3). [12][13][14][15] At birth, the ECD is approximately 5000 cells/mm 2 . 16 Studies have shown that the rate of cell loss is highest in patients younger than 10 to 20 years.…”
Section: Processes That Affect the Endotheliummentioning
confidence: 99%